Capital Markets Union - Challenges and Threats for Completion in Poland - Waliszewski, Krzysztof (Studia Oeconomica Posnaniensia, 2017)
The European Union is struggling with problems related to, inter alia, the effective stimulation of economic growth in a period of historically low interest rates. The authorities of the new mandate of the EU (2014-2019) planned a number of projects to be implemented, but the leading one is the Investment Plan for Europe. The paper is devoted to one of the initiatives under this plan - the Capital Markets Union, which is to diversify the financing structure of the SME sector in the financing market. The EU capital markets, in contrast to the banking union is planned for all countries of the EU, including Poland. The paper presents the opportunities and risks of this project in Poland.